Practice and factors associated with neonatal sunlight exposure among mothers in Jigjiga City, Somali Regional State, Eastern Ethiopia - Amal Adem Abdulahi; Mohamed Omar Osman; Yahye Mohamed Ibrahim; Ramadan Budul Yusuf; Ahmed Mohammed Ibrahim; Seid Muhumed Abdilaahi; Yusuf Hamud File; Nour Ahmed Korane; Ahmed Adem Abdullahi (BMC Pediatrics)
Abstract Background Sunlight is a vital natural resource for sustaining life on Earth. Sunlight exposure, especially ultraviolet B, is necessary for synthesizing vitamin D in the skin. Early life is the most prevalent time for vitamin D deficiency, and almost half of mothers in Ethiopia are estimated to have a low level of good practice of sunlight exposure, which remains a major contributing factor to vitamin D deficiency in Ethiopian children. Objectives To assess the practices and factors associated with neonatal sunlight exposure among mothers in Jigjiga City, Somali Regional State, Eastern Ethiopia, 2024. Methods and materials A community-based cross-sectional study was conducted among 417 mothers in Jigjiga city from April 16 to 30, 2024. The study participants were selected using a systematic random sampling technique. The data were collected using electronic data collection software (Kobo) and exported to SPSS software version 20 for analysis. Bivariable and multivariable binary logistic regression was performed. Finally, the adjusted odds ratio with a 95% confidence level was computed, and a p-value < 0.05 was used to declare statistical significance. Results Among the mothers interviewed, 29.4% with 95% CI (22.2–38.1) had good practice in exposing their neonates to sunlight. In multivariable analysis, mothers who were married (AOR = 0.17; 95% CI: 0.03–0.92), who delivered through caesarian section (AOR = 0.05; 95% CI: 0.01–0.54), who had poor knowledge of sunlight exposure (AOR = 0.31; 95% CI: 0.1–0.96) and who had no fear of sunlight exposure (AOR = 3.06; 95% CI: 1.02–9.17) were significantly associated with good practices of neonatal sunlight exposure. Conclusions This study revealed that 29.4% of mothers had good neonatal sunlight exposure practice which is low compared to other studies. The mothers’ marital status, mode of delivery, mother’s knowledge, and fear of sunlight exposure were significantly associated with the practice level of the mothers.